Socio-motivational moderators—two sides of the same coin? Testing the potential buffering role of socio-motivational relationships on achievement drive and test anxiety among German and Canadian secondary school students - Hoferichter, Frances; Raufelder, Diana; Eid, Michael (Frontiers in Psychology, 2015)
The current cross-national study investigates the potential buffering role of socio-motivational relationships for the association of achievement drive and test anxiety in secondary school students from Canada and Germany. One thousand eighty-eight students (54% girls, Mage = 13.71, SD = .53, age span 12–15 years) from the state of Brandenburg and 389 students from Quebéc (55.9% girls, Mage = 13.43, SD = .82, age span 12–16 years) were asked about their socio-motivational relationships with their teachers and peers, their drive for achievement, and test anxiety. Multigroup latent moderated structural equations (MGLMS) were conducted to test for the moderator role of socio-motivational relationships that would buffer feelings of test anxiety related to the drive for achievement. The analyses revealed the two-sided role socio-motivational relationships can have for students with different levels of achievement drive; intensifying or mitigating feelings of test anxiety. Thereby, the results of this study extend the buffering hypothesis by Cohen and Wills (1985). Cross-national differences between Canada and Germany were found concerning the studied moderators on the association of achievement drive and test anxiety: While for German students teacher-student relationships acted as moderator, for Canadian students student-student relationships and teachers acting as positive motivators displayed a moderator role.